KRITIK ATAS TANGGUNG JAWAB SOSIAL PERUSAHAAN DALAM BENCANA LUMPUR LAPINDO - Lutfi Amiruddin (Jurnal Kawistara, 2018)
In Lapindo mudflow disaster, the process of sale and purchase mechanism of sinking assets is legitimated by Presidential Decree 14/2007 (Perpres 14/2007), claimed by Lapindo as their social responsibility. In the discussion over the causes of the disaster, this scheme also raises controversy. If it was caused by an earthquake, why the company is willing to spend money to buy survivors’ assetas as form of social responsibility? On the other hand, the mechanism made conflict among the survivors. I used qualitative method; using indepth interview, observation, and literature study. I chose some informants from different side to get various perspective, such as Lapindo and survivors, in order to get the corporate social responsibility narratively and its critics. Using the concept of governmentality of Foucault, I reveal the process of Corporate Social Responsibility (CSR) in the ecological crisis in Sidoarjo is only a way to cover the mistakes that have been made, not to recover the survivors’ social and ecological conditions. The mechanism above implied to mudflow disaster management.